Diet, Mitochondrial Dysfunction, Vascular Endothelial Damage, and the Microbiome: Drivers of Ocular Degenerative and Inflammatory Diseases - Russell Phillips (Ophthalmology and Therapy)
Abstract There is abundant evidence in medical literature that Western diet and lifestyle drive the cellular and metabolic processes which underlie chronic non-communicable diseases. However, non-pharmaceutical interventions, which focus on nutrition, the microbiome and lifestyle, to prevent non-communicable diseases are not part of mainstream treatment, for a variety of reasons. Lack of progress in stemming the rise in chronic non-communicable diseases can be attributed to the current ‘downstream’ medical paradigm which is focused on treating disease and symptoms, rather than preventing disease via an ‘upstream’ approach, which looks at cause and process. Metabolic abnormalities and obesity have previously been noted as correlated with common chronic ophthalmic conditions such as age related macular degeneration (AMD), glaucoma, ocular inflammation, diabetic retinopathy and retinal vascular occlusive disease. These are ocular manifestations of an underlying common cause. The aim of this paper, using an ophthalmic context, is to provide an overview of the cellular pathophysiological mechanisms that underlie chronic non-communicable diseases, including ophthalmic diseases, and to draw the links between diet and lifestyle, the microbiome and chronic non-communicable diseases.